Вы находитесь на странице: 1из 5

# www.sakshieducation.

com

BINOMIAL THEOREM
SYNOPSIS
n

r =0

.. + nCnan.

co
m

## a) The number of terms in the expansion (x + a)n is n + 1.

b) The sum of the power of x and a in any term in the expansion of (x + a)n is n.
c) The general term in the expansion of (x + a)n is Tr + 1 = nCrxn rar.
n

C0, nC1, nC2, . nCn are binomial coefficients in the expansion of (x + a)n.

n.

2.

at
io

The binomial coefficient which are equi-distant from the beginning and from the
i.e. nC0 = nCn, nCl = nCn 1; nC2 = nCn 2 etc.

## ending are equal.

In the expansion of (x + a)n, rth term from the end is equal to (n r + 2)th terms from
the beginning.

ed
uc

3.

5.

## If C r stands for n c r , ( 1 + x) n = c 0 + c1x + c 2 x 2 +......+c n x n .

6.

In ( 1 + x) n , Tr +1 = n c r x r .

sh
i

4.

ak

np m
.
pq

9.

w
.s

8.

np
.
pq

n + 2
term.
2
th

n + 1

th

n + 3
terms.
&
2
th

## 11. Determination of numerically greatest term in the expansion of ( 1 + x) n . Consider

( n + 1)|x|
= q (say)
1+|x|

12.

If q is a positive integer, qth, (q+1)th terms in the expansion are the numerically
greatest terms in the expansion (1+x)n .

www.sakshieducation.com

www.sakshieducation.com

13.

{[ q] + 1}

th

## term is the numerically greatest term in the

expansion of (1+x)n.
14.

i)

## Numerically greatest term in (a + x)n = |a|n numerically greatest term in

n

x
1 + .

co
m

ii) If kth term is numerically greatest term in (1+x)n then x belongs to the integral

15.

n

n

## ii) General term =

( n + r 1 )

c n terms.

n!
p
p
p
a 1 1 a 2 2 ....a r r where p1 + p2+ .....+ pr = n.
p1!p 2 !....p r !

ed
uc

16.

at
io

## i) I is an odd integer ii) (I + F) (1 - F) = 1

n.

(k 1) k 1
k
k

,
,

n +1 k n + 2 k n + 2 k n +1 k

sh
i

## The sum of the coefficients in the expansion (1+x)n is obtained by putting x = 1.

18.

n
c 0 , c 1 ,c 2 , ...... c n are called the binomial coefficients in the expansion of (1+x) .

19.

c 0 + c 1 + c 2 +........+ c n = 2 n .

21.

c 0 c 1 + c 2 c 3 ................. = 0
c 0 + c 2 + c 4 +............. = 2 n 1

c1 + c 3 + c 5 +....................=

22.

w
.s

20.

ak

17.

2n-1

c1 + 2c 2 x + 3c 3 x 2 + ........ + nc n x n 1 = n(1 + x )

24.

c 1 + 2. c 2 + 3. c 3 +.........+ n . c n = n . 2 n 1

25.

c 1 2. c 2 + 3. c 3 4. c 4 + ........ = 0

26.

a) a. c 0 + ( a + d ) . c 1 + ( a + 2d ) . c 2 +..........+( a + nd ) . c n =

23.

( coefficient of c

n 1

+ coefficient of c n 2 n 1 = ( 2a + nd ) 2 n 1

www.sakshieducation.com

www.sakshieducation.com

(b) a. c 0 ( a + d ) . c1 + ( a + 2d ) . c2 ( a + 3d ) . c 3 +............ = 0
27.

c 0 c 2 + c 4 c 6 +...... = 2 n /2 cos

n
.
4

28.

c1 c 3 + c 5 c 7 + ....... = 2 n / 2 sin

n
.
4

29.

c 0 + c 4 + c 8 +.......... = 2 n 2 + 2 2 cos

30.

x2
x3
x n +1 (1 + x ) 1
c 0 x + c1
+ c2
+ ........ + c n
=
.
2
3
n +1
n +1

31.

c0 +

c1 c2
c
2 n+1 1
+ +....................+ n =
2 3
n+1
n+1

32.

c0

c1 c 2 c 3
1
+

+ ......... =
2
3
4
n +1

33.

c0 +

c2 c 4
2n
+ +....... =
3 5
n+1

34.

c1 c 3 c5
2n 1
+ + +............... =
2 4 6
n+1

35.

c 0 c r + c 1 c r + 1 + c 2 c r + 2 +..............+ c n r c n =

36.

c 1 2. c 2 3. c 3
n. c n n( n + 1)
+
+
+.........+
=
c0
c1
c2
c n 1
2

37.

c 0 2 + c 1 2 + c 2 2 +................+c n 2 = 2 n c n =

n
.
4

co
m

41.

at
io

ed
uc

ak

sh
i

2n !
( n + r) ! ( n r) !

If n is odd, c 0 2 c 1 2 + c 2 2 c 3 2 +.................... = 0
If n is even, c 0 2 c 1 2 + c 2 2 c 3 2 +............. = ( 1) n /2 n c n /2
a. c 0 2 + ( a + d ) c 1 2 + ( a + 2d ) . c 2 2 +...........+( a + nd ). c n 2 =

40.

cnr =

2n !
( n !) 2

39.

2n

w
.s

38.

n.

n +1

( 2a + nd ) ( 2 n ) !
.
.
( n !) 2
2

## If (x) = a0 + a1 x + a2 x2 ...... + anxn, then

1.a0 + a1 + a2 + ............+an = sum of all the coefficients = (1)
2. a 0 + a 2 + a 4 + ............ =

f (1) + f ( 1)
[ sum of coefficients of even powers of x ]
2

www.sakshieducation.com

www.sakshieducation.com

3. a 1 + a 3 + a 5 + ............ =

f (1) f ( 1)
[ sum of coefficients of odd powers of x ]
2

4. r. a r = f 1 (1)
r=0

42.Sum of the products of c0, c1 , c2 , ............cn taken two at a time is 22n-1 Sum of the products of 1, 2, 3, .............n taken two at a time is

44.

Sn =

f (m + n r )
r =m

n.

r =m

## Binomial theorem for rational index

at
io

f (r ) =

n (n + 1) 3n 2 n 2
24

co
m

43.

( 2n) !
.
2( n !) 2

ed
uc

## n(n 1) 2 n(n 1)(n 2) 3

n(n 1)(n 2).....(n r + 1) r
x +
x + .. +
x +
2!
3!
r!

45. (1 + x)n = 1 + nx +
.. .

sh
i

+ .. .

## n(n + 1) 2 n(n + 1)(n + 2) 3

n(n + 1)(n + 2).....(n + r 1) r
x +
x + .. +
x
2!
3!
r!

ak

46. (1 x) n = 1 + nx +

## = 1 + nC1x + (n + 1)C2x2 + .. + (n + r 1)Crxr + ..

w
.s

47. (1 x)1 = 1 + x + x2 + x3 + .. + xr + .. +
48. (1 + x) 1 = 1 x + x2 x3 + .. + (1)rxr + . +

## 50. (1 + x)2 = 1 2x + 3x2 4x3 + .. + (1)r(r + 1)xr + .

51. (1 x)3 =
52. (1 + x) 3 =

1
[1.2 + 2.3x + 3.4x2 .. + (r + 1)(r + 2)xr + ..].
1.2
1
[1.2 2.3x + 3.4x2 .. + (1)r (r + 1) (r + 2)xr + .. ].
1.2

www.sakshieducation.com

www.sakshieducation.com

=1+

p
1!

x
p ( p + q)
+
2!
q

p ( p + q )( p + 2q ).....( p + ( r 1) q )
r!

54. (1 + x)

p
q

p
=1
1!

x
+ .. +
q

x
+ .
q

x
p ( p + q)
+
2!
q

x p ( p + q )( p + 2q )

3!
q

x
+ ..
q

x p ( p + q )( p + 2q ).....( p + (r 1)q )
+(1)
+ .
r!
q

w
.s

ak

sh
i

ed
uc

at
io

n.

x
p ( p + q )( p + 2q )
+
3!
q

co
m

53. (1 x)

p
q

www.sakshieducation.com